Microplastics as vectors for virus transport in saturated quartz sand: Reduced PRD1 bacteriophage infectivity and enhanced mobility - Ahmad Ameen; Patrick J. Mikuni-Mester; Birgit Bromberger; Alexander K.T. Kirschner; Regina Sommer; Alfred P. Blaschke; Liping Pang; Margaret E. Stevenson (Journal of Hazardous Materials, 2026)

Rapid detection of Listeria monocytogenes in dairy products by a novel chemilumonogenic approach - Birgit Bromberger; Patrick-Julian Mester (Food Microbiology, 2023)

Journal Club - Yvonne Mast; Nadja Patenge; Michael Pester; Andreas Seiffert-Störiko; Volkmar Braun; Andreas Diepold; Johannes Sander; Maria Dell; Christoph Meier; Patrick Mester; Daniela Kruck; Felix Kreissl; et al. (BIOspektrum, 2022)

Resistenzbestimmung nicht-kultivierbarer Bakterien - Susanne Fleischmann; Christian Robben; Patrick Mester (BIOspektrum, 2022)
To cope with environmental stress, bacteria can enter resistant dormancy states such as the viable but non-culturable (VBNC) state, in which cells do not divide but remain alive with the potential to resuscitate. Present in both food and clinical environments, VBNC cells are a serious health risk and a challenge for conventional analytical methods. By detecting growth-independent viability parameters, it is possible to investigate resistance of VBNC cells and identify effective antimicrobials.

The physiological effects of daily cold-water immersion on 5-day tournament performance in international standard youth field-hockey players - Malte Krueger; Joseph T. Costello; Mirko Stenzel; Joachim Mester; Patrick Wahl (European Journal of Applied Physiology, 2020)

Chronic effects of superimposed electromyostimulation during cycling on aerobic and anaerobic capacity - Sebastian Mathes; Niklas Lehnen; Tobias Link; Wilhelm Bloch; Joachim Mester; Patrick Wahl (European Journal of Applied Physiology, 2017)

Markers of biological stress in response to a single session of high-intensity interval training and high-volume training in young athletes - Yvonne Kilian; Florian Engel; Patrick Wahl; Silvia Achtzehn; Billy Sperlich; Joachim Mester (European Journal of Applied Physiology, 2016)

Acute metabolic, hormonal and psychological responses to cycling with superimposed electromyostimulation - Patrick Wahl; Markus Hein; Silvia Achtzehn; Wilhelm Bloch; Joachim Mester (European Journal of Applied Physiology, 2014)

Effects of different levels of compression during sub-maximal and high-intensity exercise on erythrocyte deformability - Patrick Wahl; Wilhelm Bloch; Joachim Mester; Dennis-Peter Born; Billy Sperlich (European Journal of Applied Physiology, 2012)

Effects of bicarbonate ingestion and high intensity exercise on lactate and H+-ion distribution in different blood compartments - Christoph Zinner; Patrick Wahl; Silvia Achtzehn; Billy Sperlich; Joachim Mester (European Journal of Applied Physiology, 2011)

Effects of acid–base balance and high or low intensity exercise on VEGF and bFGF - Patrick Wahl; Christoph Zinner; Silvia Achtzehn; Michael Behringer; Wilhelm Bloch; Joachim Mester (European Journal of Applied Physiology, 2011)